Assessment of Solar Climate Resources on the Territory of the Republic of Moldova in the Context of Climate Change - BEJENARU, Gherman; DILAN, Vitalie (Studia Universitatis Babeș-Bolyai Geographia, 2025)
Assessment of Solar Climate Resources on the Territory of the Republic of Moldova in the Context of Climate Change. This study evaluates the solar climate resources of the Republic of Moldova in the context of climate change. The analysis covers data from representative meteorological stations for the periods 1961-1990 and 1991-2020. The main focus is on global and direct solar radiation, as well as sunshine duration. Results indicate an increasing trend in solar radiation and sunshine duration, particularly in the northern part of the country. The study also discusses the implications for the use of solar energy in Moldova, highlighting the potential for enhanced heliothermal resources due to climate change. The findings provide a comprehensive understanding of solar climate variations and their impact on renewable energy potential.